Gene Therapy of Autoimmune Disease - Prud'homme, Gerald J. (Medical Intelligence Unit, 2005)
Autoimmune diseases are diverse and responsible for considerable morbidity. Their etiology remains largely unknown, and current therapy with anti-inflammatory drugs is prone to adverse effects, and rarely curative. New therapies with anti-cytokine antibodies or receptors are promising, but require frequent administration of expensive protein drugs. Gene Therapy of Autoimmune Diseases comprehensively reviews research in gene therapy for autoimmune diseases with viral or non-viral vectors. Gene therapy offers the possibility of long-term, continuous delivery of a wide variety of immunosuppressive, anti-inflammatory, or tolerance-inducing agents. Moreover, highly specific genetically modified cells can be produced. This book discusses the most promising avenues in this exciting new field.